A direct analytical and exact synthesis for multi‐section impedance transformers. Issue 12 (15th September 2021) - Xie, Yuqiang; Li, Xiuping; Li, Qingwen; Qi, Zihang
Abstract: In this article, a novel direct analytical and exact synthesis for the multi‐section transformers with arbitrary real‐to‐real transforming ratio is proposed. Compared with the conventional small reflection theory, the proposed one features an exact solution and design flexibility. Based on the new method, the direct solution for a three‐section maximally flat transformer is presented for the first time. And the Remez iteration method is introduced to obtain the multiband Chebyshev response transformers. For validation, a tri‐band Chebyshev impedance transformer was designed and fabricated. The simulated and measured results agree with each other.